Social perception of tree plantations in the Atlantic forest of Argentina: the role of management scale - Cariola, Lucía; Izquierdo, Andrea E.; Hilgert, Norma I. (Ethnobiology and Conservation, 2018)
Land use changes associated with the advance of forest plantations on lands previously used for agriculture generate diverse perceptions of the socio-environmental impact they entail. In last decades there has been a transformation in land use associated with the development of forestry activity in the northwest of the province of Misiones, Argentina. Considering local communities in order to improve assessment, governance and decision-making in sustainable management, we posed two questions: What are local communities’ environmental, social and economic perceptions of tree plantations? What is the role of scale of production in these perceptions? To this purpose we first described the productive matrix of the landscape mapping the forest plantation cover of the area and classifying the productive units in different Forest Management Model (large, medium and small scale). Then, we identified and selected participants from comparable rural communities in each FMM, who through a Q survey grouped phrases according their perceptions. Subsequently, emerging viewpoints were recognised. Our analysis shows that forestry activity is not poorly conceptualized in contrast to conceptualization of the management of larger-scale productive systems in combination with government policies promoting them. The management carried out through large areas that result in a homogenization of the landscape are perceived negatively. In general terms, the local imagination perceives the promotion and establishment of forestry companies as a mistake if planning to protect pre-existing familiar productive systems is not previously carried out.